THE INFLUENCE OF STUDENTS' PERCEPTION AND LEARNING DISCIPLINE TOWARDS ENGLISH LEARNING ACHIEVEMENT - Tia Karlina; Gola Kusnarti (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2022)
The purpose of this research was to determine the influence of students' perception and learning discipline on their school towards English learning achievement, the influence of students' perception towards English learning achievement, and the influence of learning discipline towards English learning achievement. The research method was descriptive survey method, which is a research method that takes a sample from a population and used a questionnaire as a data collection tool. The number of samples were 2 classes from 2 schools, namely the Mulia Hati Insani Warunggunung Private Vocational School, and the Matala'ul Anwar Cibuah Vocational School. The results of this research indicated that: 1) There is a significant effect of students' perception and learning discipline towards English learning achievement at Private Vocational Schools, Lebak Regency, Banten Province. This is evidence by the acquisition of the value of Sig. 0.043 < 0.05 and F count = 8.329. 2) There is an insignificant effect of students' perception towards English learning achievement at Private Vocational School, Lebak Regency, Banten Province, this is evidence by the acquisition of the value of Sig. 0.679 > 0.05 and t count = 0.415. 3) There is a significant influence of learning discipline towards English learning achievement at Private Vocational Schools, Lebak Regency, Banten Province. This is evidence by the acquisition of Sig. 0.038 < 0.05 and t count = 2.869. The result of students’ perception towards English learning achievement is an insignificant effect in this research, due to students’ perception is related to students’ internal and external factors. This factor determines students’ learning outcomes, especially in learning English. Therefore, students’ perception must always be pursued, grown, and maintained by all educator personnel.